Petrogenesis and thermal overprint of S-type granites in Helanshan region, North China Craton: Constraints on the 1.90Ga khondalites decompression melting and 1.32Ga tectono-thermal event - Zhang, Dao-Han; Schmitt, Axel Karl (Precambrian research, 2017)
Widespread Paleoproterozoic S-type granites and khondalites (high-grade sillimanite-garnet gneisses) are exposed in the Khondalite Belt of the North China Craton (NCC). Porphyritic biotite granites in the Helanshan region from the western Khondalite Belt exhibit a gradual contact relationship with the neighboring khondalites. In order to constrain the petrogenesis of these granites and their genetic relationship with the khondalites, detailed geochronological data, as well as geochemical and whole-rock Sm-Nd and zircon Lu-Hf isotope compositions of these granites are reported. LA-ICP-MS zircon U-Pb dating on magmatic zircon cores yields an emplacement age of 1902±22Ma, whereas metamorphic rims define a metamorphic age of 1356±57Ma. The unpolished surfaces of zircon crystals selected based on the presence of rims visible in cathodoluminescence were further analyzed by SIMS depth profiling, which gave a more precise metamorphic age of 1317±18Ma. The Helanshan granites display typical S-type geochemical characteristics, e.g., high A/CNK (1.16-1.29) and K2O (5.09-5.86wt%) contents, but low FeOt/MgO (2.39-4.88) and P2O5 (0.15-0.23wt%) contents. Similar trace and rare earth element patterns, and consistent zircon Hf model ages (2366-2483Ma) and whole rock Nd model ages (2407-2499Ma) between the porphyritic biotite granites and the khondalites, suggest that they were derived from partial melting of khondalites. The geochemical character of the porphyritic biotite granites, including significant negative Eu anomalies, high Rb/Ba and Rb/Sr ratios, and variable HREE contents and (La/Yb)N ratios, suggest that they are probably related to the post-peak decompression stage that was characterized by biotite breakdown and the progressive replacement of garnet with the presence of K-feldspar and plagioclase in the residues. Homogeneous zircon εHf(t) values (mostly from −0.5 to +1.7), combined with low bulk-rock Fe2O3T content and CaO/Na2O ratios, preclude the contribution from mafic magma. Following the continental collision, the emplacement of the porphyritic biotite granites at ca.1.90Ga provides the latest limit on the timing of post-peak decompression metamorphism of the khondalites, and their formation supports a post-collisional mantle upwelling model to account for the 1.92-1.90Ga regional metamorphic/magmatic events. On the other hand, the metamorphic zircon rims indicate that S-type granites were overprinted by a 1.32Ga tectono-thermal event, which was probably related to the breakup of the Columbia supercontinent.